Memperkuat Integrasi Nasional Melalui Generasi Bangsa dan Teknologi Pada Pembelajaran Pendidikan Kewarganegaraan - Makruf Makruf; Muhammad Zidan Firmansyah; Sasmi Nelwati (Badan Penerbit STIEPARI Press, 2024)
Abstract Strengthening National Integration Through National Generation and Technology in Citizenship Education Learning National integration has been going on since ancient times until now, with continuity and rapid development. The aim of this research is to find out whether a sense of nationalism still exists in the nation's generation. The method used is data collection from relevant journals with the title